2014
DOI: 10.1186/1471-2458-14-171
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and instrumental feeding practices of Dutch mothers regarding foods eaten between main meals

Abstract: BackgroundTo assess how much of a public health problem emotional and instrumental feeding practices are, we explored the use of these feeding practices in a sample of Dutch mothers regarding their child’s food intake between main meals.MethodsA cross-sectional questionnaire study was conducted among 359 mothers of primary school children aged 4–12 years. The questionnaires were completed online at home.ResultsOf the mothers, 29.5% reported using foods to reward, 18.1% to punish and 18.9% to comfort their chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 25 publications
4
40
3
2
Order By: Relevance
“…'Reward for good behaviour' was the participants' primary motivation for treat food provision, in accordance with previous knowledge that the use of foods for behavioural control is a common practice among parents and teachers (Blaine et al, 2015;Kubik, Lytle, Hannan, Story, & Perry, 2002;Raaijmakers, Gevers, Teuscher, Kremers, & van Assema, 2014). Research has shown that using unhealthy foods as a reward or an emotion control instrument may reinforce children's preference of those foods, and may increase the risk of dietary disorders, such as binge eating, emotional eating and dietary restraint (Benton, 2004;Farrow, Haycraft, & Blissett, 2015;Puhl & Schwartz, 2003).…”
Section: Significance Of the Results And Implicationssupporting
confidence: 81%
“…'Reward for good behaviour' was the participants' primary motivation for treat food provision, in accordance with previous knowledge that the use of foods for behavioural control is a common practice among parents and teachers (Blaine et al, 2015;Kubik, Lytle, Hannan, Story, & Perry, 2002;Raaijmakers, Gevers, Teuscher, Kremers, & van Assema, 2014). Research has shown that using unhealthy foods as a reward or an emotion control instrument may reinforce children's preference of those foods, and may increase the risk of dietary disorders, such as binge eating, emotional eating and dietary restraint (Benton, 2004;Farrow, Haycraft, & Blissett, 2015;Puhl & Schwartz, 2003).…”
Section: Significance Of the Results And Implicationssupporting
confidence: 81%
“…For instance, use of food as reward is more prevalent among mothers in low-income families (Hendy & Williams, 2012). However, others report that use of food as a reward is associated with high maternal education as was the case for increasing African-American fathers’ education and use of food as a reward in the current study (Raaijmakers et al, 2014). …”
Section: Discussionmentioning
confidence: 43%
“…Among young children up to 12 months in age, sweetened drinks were more likely to be offered as a reward or as a treat for good behavior (Hoare et al, 2014). Similarly, sweets (i.e., candy, ice cream), nuts, and savory snacks were more frequently offered as rewards to children aged 4-12 years (Raaijmakers, Gevers, Teuscher, Kremers, & van Assema, 2014). Although a number of studies have described parents’ use of unhealthy foods or beverages in the context of instrumental and emotional feeding, associations have been predominantly reported by mothers.…”
Section: Discussionmentioning
confidence: 99%
“…However, instrumental and emotional feeding are not always related. It would be interesting to study this parenting practice in more detail by looking into differences between using food in between meals to regulate a child’s emotions (emotional feeding) and using food as a reward or withholding food as a punishment (instrumental feeding) [31]. Awareness and lack of self-efficacy may be regarded as precursors of parenting practices instead of actual parental behaviours.…”
Section: Discussionmentioning
confidence: 99%